Rehabilitation Policy as Treatment for Narcotics Addicts (Study at the BNN Kalianda South Lampung Rehabilitation Workshop) - Bahara Rizki (LEGAL BRIEF, 2018)
Abuse and illegal circulation of narcotics is already up to a degree of concern for it to the addicts to do rehabilitation to relieve addicts from narcotic dependence. The problem in this study is: what is the basis of legal considerations of judges in dropping a rehabilitation decision as a treatment of narcotics and how to rehabilitation policy as a treatment of narcotics prevention is carried out by the BNN Kalianda Rehabilitation Workshop. The approach to the problem used in this study is to use normative and empirical juridical approaches. The speakers in this study were the judges of the District Court, head of rehabilitation and academics of the Faculty of Law of Lampung University. The results showed that: (1) The basis of legal considerations in dropping a rehabilitation decision as a treatment of narcotics is based on juridical considerations, which are laws, indications, letter Claims, witness information and information of defendants and the basis of non-juridical considerations are based on the wisdom and conviction of a judge's conscience, self-condition, socio-economic conditions and polite nature. (2) The policy carried out by rehabilitation workshop in conducting rehabilitation as treatment is: (a) intensifying policy must report narcotics addicts executed successfully. (b) Both medical and social treatment and rehabilitation service policies have been successfully executed. (c) The policy of advanced coaching to victims of abuse and drug addicts through treatment and rehabilitation of relatively well-being and effective in accordance with existing laws and regulations. The advice in this study is that law enforcement officers should perform tasks can be objective, local governments should maximize the functions of social institutions in relation to rehabilitation policy, resident should be Reporting for voluntary rehabilitation treatment and the public should always supervise.